A Comparison of Algorithms for Solving the Multiagent Simple Temporal Problem - Boerkoel Jr., James; Durfee, Edmund (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
The Simple Temporal Problem (STP) is a popular representation for solving centralized scheduling and planning problems. When scheduling agents are associated with different users who need to coordinate some of their activities, however, considerations such as privacy and scalability suggest solving the joint STP in a more distributed manner. Building on recent advances in STP algorithms that exploit loosely-coupled problem structure, this paper develops and evaluates algorithms for solving the multiagent STP. We define a partitioning of the multiagent STP with provable privacy guarantees, and show that our algorithms can exploit this partitioning while still finding the tightest consistent bounds on timepoints that must be coordinated across agents. We also demonstrate empirically that our algorithms can exploit concurrent computation, leading to solution time speed-ups over state-of-the-art centralized approaches, and enabling scalability to problems involving larger numbers of loosely-coupled agents.